Parametric Analysis and Control of Bedding-Inclined Asymmetric Stress in Double-Arch Tunnels: A 3DEC-Based Study on Jointed Rock Masses - Pai Zhang; Wangrong Li; Liqiang Xu; Fengwei Wu; Zaihong Li; Pei Tai; Leilei Liu (Buildings)
Double-arch tunnels in inclined layered jointed rock masses face risks of lining cracking and collapse under bedding-inclined asymmetric stress (BIAS); however, related studies remain limited. Based on a case study of an expressway tunnel case in Zhejiang Province, a three-dimensional discrete element model of a double-arch tunnel was developed using Three-Dimensional Distinct Element Code (3DEC) (version 7.0, Itasca Consulting Group, Inc., Minneapolis, MN, USA). The impacts of joint dip angle (0–90°) and spacing (0.5–6.5 m) on deformation, BIAS evolution, and middle partition wall stability were analyzed. Key findings reveal that joint presence significantly amplifies surrounding rock deformation, with pronounced displacement increases observed on the counter-dip side. The BIAS intensity follows a unimodal distribution with joint dip angles, peaking within the 30–60° range. Increasing joint spacing reduces BIAS effects, with a 57.1% decrease in asymmetric deformation observed when spacing increases from 0.5 m to 6.5 m. The implementation of dip-side pilot excavation with the main tunnel full-face method, combined with an optimized support strategy (installing dip-side bolts perpendicular to joints and extending counter-dip side bolt lengths from 4 m to 6 m), achieved a near-unity stress ratio between tunnel sides under equivalent overburden depths compared to conventional methods. These findings offer theoretical and technical insights for optimizing excavation and reinforcement in similar tunnel engineering contexts.